Methodological Opportunities for Improving the Quality of Higher Education Institution - Nikolett Mihály; Katalin Tari (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
As a consequence of the demographic tendencies of the developed countries the competition between higher education institutions is more and more intense in order to have and hold students. In this way they are interested in surveying their students' expectations and satisfaction to find out how and where to improve the institutions while the research also serves other purposes, as well. The present study is aimed at analysing the examinations directed at service quality assessment in higher education. The expectations, experience and the significance of further evaluations are examined. The analyses has happened with the help of literature overview and own quantitative researches. Results show that expectations and satisfaction are rather influenced by personality traits and the type of the given faculty topic than the real competencies.
Keywords: I00; M1; 330; management; development; quality; education